2020
DOI: 10.48550/arxiv.2003.14055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matui's AH conjecture for Graph Groupoids

Abstract: We prove that Matui's AH conjecture holds for graph groupoids of infinite graphs. This is a conjecture which relates the topological full group of an ample groupoid with the homology of the groupoid. Our main result complements Matui's result in the finite case, which makes the AH conjecture true for all graph groupoids covered by the assumptions of said conjecture. Furthermore, we observe that for arbitrary graphs, the homology of a graph groupoid coincides with the K-theory of its groupoid C * -algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…The same goes for transformation groupoids associated to odometers [Sca18], which incidentally, provided counterexamples to the other conjecture from [Mat16], namely the HK conjecture. In the recent paper [NO20], we showed that the AH conjecture holds for graph groupoids of infinite graphs, complementing Matui's result in the finite case [Mat15].…”
supporting
confidence: 68%
See 4 more Smart Citations
“…The same goes for transformation groupoids associated to odometers [Sca18], which incidentally, provided counterexamples to the other conjecture from [Mat16], namely the HK conjecture. In the recent paper [NO20], we showed that the AH conjecture holds for graph groupoids of infinite graphs, complementing Matui's result in the finite case [Mat15].…”
supporting
confidence: 68%
“…In the case that B = 0 the map ϕ : H 0 H A,0 → H 0 H A,0 coincides the inverse δ −1 of Matui's map δ from [Mat15, page 56]. See Remarks 7.6 and 8.8 in [NO20] for more on this.…”
Section: A Long Exact Sequence In Homologymentioning
confidence: 89%
See 3 more Smart Citations